Comparison of Methods for Monitoring Intra-operative Cerebral Perfusion in Patients Undergoing Carotid Endarterectomy with Selective Shunting: A Systematic Review and Network Meta-Analysis of Randomised Controlled Trials and Cohort Studies. (February 2023) - Jovanovic, Aleksa; Jonsson, Magnus; Roy, Joy; Eriksson, Julia; Mutavdzic, Perica; Trailovic, Ranko; Koncar, Igor
Abstract : Objective: This study aimed to analyse the influence of different methods of monitoring cerebral perfusion (MCP) on stroke, death, and use of intraluminal shunt during carotid endarterectomy (CEA). Methods: A systematic review and network meta-analysis was conducted and registered in the PROSPERO registry (CRD42021246360). Medline, Embase, CENTRAL, and Web of Science were searched. Randomised controlled trials (RCTs) and cohort studies with > 50 participants that compared clinical outcomes for different MCP in patients undergoing CEA were included. Papers reporting one or a combination of two of the following MCPs were included in the analysis: awake testing (AT), near infrared spectroscopy (NIRS), electroencephalography (EEG), somatosensory evoked potential (SSEP), motor evoked potential (MEP), transcranial Doppler (TCD), and stump pressure (SP). A random effects network meta-analysis was performed using a binomial likelihood function with a specified logit link for peri-operative stroke or death and shunting as outcomes. Near infrared spectroscopy was excluded due to the lack of studies that could be used for statistical analysis. Results: Of 1 834 publications, 17 studies (15 cohort studies and two RCTs) including 21 538 participants were incorporated in the quantitative analysis. Electroencephalography was used in the largest number of participants (7 429 participants, six studies), while AT was used in the highest number of studies (10 studies). All monitoring modalities had worse outcomes with respect to stroke or death when compared with AT, with ORs ranging between 1.3 (95% credible interval [CrI] 0.2 – 10.9) for SSEP + MEP and 3.1 (CrI 0.3 – 35.0) for patients monitored with a combination of EEG and TCD. However, the wide CrI indicated that there is no statistically significant difference between the monitoring methods. Patients monitored with a combination of EEG and TCD had the lowest odds of being shunted, while SP had the highest odds of being shunted, also with no statistically significant difference. Conclusion: There is a lack of high quality data on this topic in the literature. The present study showed no significant difference between monitoring methods investigated in the network meta-analysis.